PENGARUH PERUBAHAN PENGGUNAAN LAHAN TERHADAP KONDISI HIDROLOGI DAS KONAWEHA HULU PROVINSI SULAWESI TENGGARA - Baco, La; Sinukaban, Naik; Purwanto, Yanuar J; Sanim, Bunasor; Tarigan, Suria Darma (Jurnal Agroteknos, 2011)
ABSTRACT Phenomena of depleting of water resources and increasing water demand have been occurring in Konaweha watershed. Combine with other conditions, Konaweha watershed have been categorized as priority watershed in Southeast Sulawesi Province. Land use change is  presumed to  influence hydrology conditions such as  the  increasing maximum discharge in rainy season, decreasing minimum discharge in dry season and also runoff coefficient increased in rainy season. The objective of this research was to evaluate the effects of land use changes on hydrology conditions such as maximum discharge, minimum discharge and runoff cpeficient. This research was conducted at Konaweha watershed for 10 months from June 2009 to March 2010.   The result of this research showed that forest, swamp,  plantation  and  bush  area  tended  to  decline  exponentially year  by  year  due  to population growth. During 1991 to 2010 forest decresed from 66,6 % in 1991 to 48,3 % in 2010. At the same time, plantation, mix garden and bush increased 26,0 % to 39,7 %, 3,0 % to 5,0 %, and 1,7 % to 3,1 % from the total of the watershed area.   The decline of forest area have significantly decreased minimum discharge of Konaweha River in dry season from 40 m3/second in 1991 to 24 m3/second in 2010. At the same time, maximum discharge increased from 246 m3/second to 284 m3/second, and runoff coefficient increased from 31,4% to 48,3 %. Key words: watershed, land use change, discharge, runoff coeficient